2016
DOI: 10.1097/wno.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt–Chromium Metallosis With Normal Electroretinogram

Abstract: Background Ocular cobalt toxicity is a rare phenomenon reported with increased frequency due to the rise of cobalt-chromium metal hip implants. We report the case of a 66 year-old previously healthy man who developed decreased vision due to cobalt-chromium toxicity from a metal-on-metal hip arthroplasty. Our objective was to determine whether the origin of his visual loss was due to toxicity of the optic nerve, of the retina, or of both. Methods Ocular examination, 10–2 SITA-Standard Humphrey Visual Field (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Metallosis is defined as aseptic fibrosis, local necrosis, or loosening of a device secondary to metallic corrosion and release of wear debris [5]. It can be related to many different types of metal implants, such as titanium [5,6], cobalt/chromium [6][7][8] or different joint replacements such as hip, knee and shoulder [6,[9][10][11][12].…”
Section: Terminologymentioning
confidence: 99%
“…Metallosis is defined as aseptic fibrosis, local necrosis, or loosening of a device secondary to metallic corrosion and release of wear debris [5]. It can be related to many different types of metal implants, such as titanium [5,6], cobalt/chromium [6][7][8] or different joint replacements such as hip, knee and shoulder [6,[9][10][11][12].…”
Section: Terminologymentioning
confidence: 99%
“…The composite score for ocularvestibular symptoms increased from 54% to 57%-68% with rising threshold value (120-170 or 220 nmol/L), which suggests a correlation between ion concentration and symptomprevalence. Subjects in the current study reported tinnitus and hearing loss far more often than patients in the general population [53,56,57]. Also, more subjects were found with tinnitus in the high cobalt ionconcentration group at higher thresholds and with increasing threshold values.…”
Section: Cobalt Toxicitymentioning
confidence: 58%
“…These concentrations might be influenced by a variety of parameters, which can be divided into patient factors (female sex, age at surgery (young), time since implantation), implant factors (bilateral, small femoral HRA components, design, type of implant (HRA/LHMoM)) and surgical factors (acetabular component malposition, reduced contact patch to rim distance) [55]. There was a concern that increased cobalt and chromium ion concentrations increased the risk for cancer, but this was proven otherwise in large comparative studies [56,57]. Nevertheless, in 2012, the NetherlandsOrthopaedicAssociation (NOV) advised against the use of any MoM hip arthroplasty [58,59].…”
Section: Metal-on-metal Issuesmentioning
confidence: 99%